Pengaruh Return On Asset (Roa) dan Price To Book Value (Pbv) terhadap Return Saham - Salma Nisya Pratiwi; Lasmanah; Azib (Bandung Conference Series: Business and Management, 2022)
Abstract. This study aims to examine the effect of Return on Assets (ROA), and Price to Book Value (PBV) on Stock Returns. The object used in this study is the pharmaceutical industry sector which is listed on the Indonesia Stock Exchange (IDX) in 2017-2021. The method used in this study is verification and data analysis using panel data regression. This study uses 7 samples of companies in the pharmaceutical industry sector from a total population of 10 companies which were taken using purposive sampling technique with the 2017-2021 research period. The results showed that simultaneously, return on assets and price to book value had an effect on stock returns. While partially return on assets has an influence on stock returns. Likewise, Price to book value has an influence on stock returns. Abstrak. Penelitian ini bertujuan untuk menguji pengaruh Return on Asset (ROA), dan Price to Book Value (PBV) terhadap Return Saham. Objek yang digunakan dalam penelitian ini adalah sektor industri farmasi yang terdaftar di Bursa Efek Indonesia (BEI) pada tahun 2017-2021. Metode yang digunakan dalam penelitian ini verifikatif dan analisis data menggunakan regresi data panel. Penelitian ini menggunakan 7 sampel perusahaan pada sektor industri farmasi dari jumlah populasi 10 perusahaan yang diambil menggunakan teknik purposive sampling dengan periode peneltian 2017-2021. Hasil penelitian menunjukkan bahwa secara simultan, return on asset dan price to book value memiliki pengaruh terhadap return saham. Sedangkan secara parsial return on asset memiliki pengaruh terhadap return saham. Begitu juga dengan Price to book value memiliki pengaruh terhadap return saham.